2019
DOI: 10.3390/molecules24091839
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Myricitrin and 3,5-di-O-Methyl Gossypetin from Syzygium samarangense and Evaluation of their Involvement in Protecting Keratinocytes against Oxidative Stress via Activation of the Nrf-2 Pathway

Abstract: The wax apple (Syzygium samarangense) is traditionally employed as an antibacterial and immunostimulant drug in traditional medicine. This plant is rich in different flavonoids and tannins. In this study, we isolated two compounds from S. samarangense leaves: myricitrin and 3,5-di-O-methyl gossypetin. Then, we investigated the mechanisms of action of the two compounds against oxidative stress (induced by sodium arsenite) and inflammation (induced by UV light) on human keratinocytes. We could clearly demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 32 publications
3
23
0
Order By: Relevance
“…Apigenin also facilitates nuclear translocation in human retinal epithelial ARPE-19 cells at concentrations higher than those physiologically available in humans [ 95 , 101 ]. Similarly, butein upregulates Nrf2 nuclear translocation against hydrogen peroxide-induced oxidative stress in human dental pulp cells [ 55 , 130 ]. Further, due to the lack of availability of clinical data on the bioavailability of butein, the physiological relevance of tested concentrations of butein is mostly unknown.…”
Section: Role Of the Nrf2/are Pathway In Cancer Chemopreventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apigenin also facilitates nuclear translocation in human retinal epithelial ARPE-19 cells at concentrations higher than those physiologically available in humans [ 95 , 101 ]. Similarly, butein upregulates Nrf2 nuclear translocation against hydrogen peroxide-induced oxidative stress in human dental pulp cells [ 55 , 130 ]. Further, due to the lack of availability of clinical data on the bioavailability of butein, the physiological relevance of tested concentrations of butein is mostly unknown.…”
Section: Role Of the Nrf2/are Pathway In Cancer Chemopreventionmentioning
confidence: 99%
“…However, the activation of the Nrf2/ARE pathway has not always been beneficial because the same flavonoids may promote the growth of cancer cells as well [ 52 ]. In normal cells, chemoprevention can be achieved by expressing Nrf2/ARE-driven cytoprotective genes [ 34 , 35 , 37 , 53 , 54 , 55 ]. However, a study conducted by Harris and colleagues in 2015 showed that the biosynthesis of cytoprotective molecules glutathione (GSH) and thioredoxin synergistically facilitates cancer initiation and progression in genetically engineered mice of mammary tumor initiation [ 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 Phytochemical constituents [46,47], 2′,4′-dihydroxy-6′-methoxy-3′-methylchalcone or stercurensin (7), 2′-hydroxy-4′,6′-dimethoxy-3′-methylchalcone (8) [46,47], 2′,4′-dihydroxy-6′-methoxy-3′,5′dimethylchalcone (9) [44], 2′,4′-dihydroxy-3′,5′-dimethyl-6′-methoxychalcone (10), 2′,4′-dihydroxy-6′-methoxchalcone or cardamonin (11) [51], pinocembrin (12), (−)-strobopinin (13), 8methylpinocembrin (14), demethoxymatteutcinol (15), 7hydroxy-5-methoxy-6,8-dimethylfoavanone (16) [48], 7,8,3′,4′-tetrahydroxy-3,5-dimethoxyflavone (17) [45], 7-hydroxy-5-methoxy-6,8-dimethylflavanone (18), quercetin (19) [49,50], kaempferol (20) [54], gallocatechin (21), myricetin…”
Section: Syzygium Guineensementioning
confidence: 99%
“…Myricetin-3-O-rhamnoside (29) [43,45], europetin-3-rhamnoside (30) [43], mearnsitrin (31) [53], reynoutrin (32), hyperin (33)…”
Section: Flavonoid Glycosidesmentioning
confidence: 99%
“…As a transcription factor, Nrf2 is downregulated under oxidative stress environment. Numerous antioxidant therapies have the function to activate Nrf2-related signaling pathways [38][39][40]. Evidence has shown the lower expression of Nrf2 in OSA patients or the IH animal models [41,42].…”
Section: Effect Of Tsa On Nrf2 and Nf-kb Expressionmentioning
confidence: 99%